Intercultural Communication Competence Of Street Vendors In Kuta Mandalika: A Qualitative Study - Nusa, M. Andre Ekha; Baharuddin; Wardana , Lalu Ali (Journal of Authentic Research, 2026)
This study explores the intercultural communication competence (ICC) of street vendors in Kuta Mandalika when interacting with foreign tourists. Using a qualitative approach and the Developmental Model of Intercultural Sensitivity (DMIS) framework, the study involved 12 vendors through semi-structured interviews and field observations. The results showed that the majority of traders were at the Adaptation stage (66.6%), while the rest were at the Acceptance (16.7%) and Minimisation(16.7%) stages. The vendors applied multimodal strategies such as using simple English, gestures, visual aids (calculators), and peer collaboration to overcome communication barriers. The study concludes that the communication competencies of the traders develop dynamically through experiential learning in their daily interactions, rather than through formal education. These findings emphasise the importance of strengthening the communication competencies of informal sector workers to support the professional image of Mandalika as a competitive global tourism destination.